Cybervictimization and non-suicidal self-injury among Chinese adolescents: The effect of depression and school connectedness - Liu, Sui; Wu, Wanchun; Zou, Hongyu; Chen, Yanrong; Xu, Liling; Zhang, Wei; Yu, Chenfu; Zhen, Shuangju (Frontiers in Public Health, 2023)
Cybervictimization has been shown in many studies to be a risk factor for adolescent non-suicidal self-injurious behavior (NSSI). In this study, we tested the roles of depression and school connectedness in this association. The Integrative Model of NSSI, the Emotion Regulation and Interpersonal Relationship Model of NSSI, and the Integrative Model of Social Media and Suicide provided the conceptual framework for the study. A sample of 1106 adolescents (Mage = 13.17; SD = 0.69; 51.78% girls) completed anonymous questionnaires in their classrooms. The results of structural equation modeling showed that the positive association between cybervictimization and adolescent NSSI was mediated by depression. Moreover, this indirect link was stronger for adolescents with low vs. high school connectedness. The results have implications for intervention programs aimed at reducing NSSI among adolescents.